(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1869)
The author contrasts the contemporary dimnesions of a ruined site in the Lammermuir hills with descriptions from the eighteenth century. The similarity of this structure to a broch is noted, although the author does acknowledge that Edin’s Hall is significantly larger and that there are no other broch-like structures nearby. He concludes by detailing the landowner’s plans for the conservation of the site and proposes that the Society should excavate and map the site once these plans have been completed.